2013
DOI: 10.1080/15287394.2013.821396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corexit Dispersants on Cytotoxicity Parameters in a Cultured Human Bronchial Airway Cells, BEAS-2B

Abstract: The objective of this study was to assess the cytotoxicity of COREXIT dispersants EC9500A, EC9527A, and EC9580A on human airway BEAS-2B epithelial cells. Cells were exposed to dispersants for 2 or 24 h at concentrations ranging from 0 to 300 ppm. COREXIT EC9527 at 100 ppm produced 50% viability loss as measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) at 24 h. COREXIT 9527 at 200 ppm produced 50% cell death at 2 h and 100% at 24 h. At 300 ppm COREXIT 9527 induced 100% cell death at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…As previously demonstrated, WAF-dispersed oil is more toxic than WAF-crude oil (Shi et al, 2013), and exposure to Corexit dispersant is toxic (Shi et al, 2013) and causes DNA damage (Fig. 2).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…As previously demonstrated, WAF-dispersed oil is more toxic than WAF-crude oil (Shi et al, 2013), and exposure to Corexit dispersant is toxic (Shi et al, 2013) and causes DNA damage (Fig. 2).…”
Section: Discussionmentioning
confidence: 60%
“…Previous data demonstrated that exposure of BEAS-2B cells to low concentrations (100–300 ppm) of Corexit EC9527A and EC9500A dispersants significantly reduced cell viability after 2 h and eliminated almost 100% of the cell culture by 24 h (Shi et al, 2013). To determine the influence of dispersants the WAF-dispersed oil samples, cell viability of BEAS-2B cell following treatment with the WAF-crude, WAF-9500 + oil and WAF-9527 + oil mixed samples was investigated using the MTT assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to define the lower limit of detection imposed by the toxicity of chemical disinfectants on cell cultures (22). Since Corexit 9500 has been shown to be cytotoxic to mammalian (9) and fish (23) cells in culture, the effect of the oil dispersant on the viability of the two fish cell lines, EPC and CHSE-214, that were used to monitor the viruses after their exposure to Corexit 9500 was examined. Corexit 9500 at a starting concentration of 10% (vol/vol) was serially diluted in a mock TCID 50 assay from 10 Ϫ1 to 10 Ϫ6 ; the 10 Ϫ1 TCID 50 dilution corresponded to a Corexit 9500 concentration of 1%, 10 Ϫ2 to 0.1%, 10 Ϫ3 to 0.01%, 10 Ϫ4 to 0.001%, 10 Ϫ5 to 0.0001%, and 10…”
Section: Resultsmentioning
confidence: 99%
“…For human health, the research has ranged from clinical assessments (8) to studies of cell lines (9). For the environment, the possible influence of dispersants on a range of metazoans, including corals, crustaceans, mollusks, fish, and birds (7,10,11), has been investigated.…”
mentioning
confidence: 99%